Comparative programming languages : generalizing the programming function - Friedman, Linda Weiser (Englewood Cliffs, New Jersey : Prentice-Hall, 1992)
This is a book for problem solvers working within the programming function, an area that can encompass such diverse tasks as software system design and development, language selection, testing and debugging, documentation, data design, training and evaluating software products.
Preface -- Part 1. Elements of Programming Languages -- Part 2. Programming Languages for Information Processing -- Part 3. Other Programming Tools and Environments -- Appendices -- Index.
Includes bibliographical references and index.
Keywords: PROGRAMMING LANGUAGES (ELECTRONIC COMPUTERS)